Role of Green Finance, Trade Openness, FDI, Economic Growth on Environmental Sustainability in Pakistan - Khizar, Sana; Anees, Alvena (iRASD Journal of Economics, 2023)
With time, the world is concerned about environmental protection and climate change, so policymakers and researchers focus on green finance. We investigate the role of green finance, GDP, trade openness, and foreign direct investment on environmental sustainability in Pakistan from the period from 1980 to 2020. By applying the autoregressive distributed lag model (ARDL) we find that green finance, GDP, and foreign direct investment are a positive and significant relationship with environmental sustainability while trade openness is a negative and insignificant effect on environmental sustainability. According to the theory of the environmental Kuznets curve, a model of environmental sustainability is developed.